Análise bioclimática e investigação do conforto térmico em ambientes externos: uma experiência no bairro de Petrópolis em Natal/RN - Costa, Angelina Dias Leão (2003)
This study was intended to investigate how the urban form has been influencing the changes in the climate of the city and make a correlation between the climate and the thermal sensation of the users of open spaces. The research was developed in the district of Petrópolis in Natal/ RN whose occupation has been almost consolidated. Among other reasons, this district was selected because it was planned considering the environmental aspects of comfort. The methodologies used are based on KATZSCHNER (1997) and OLIVEIRA (1988) studies, which suggest the drawing and analysis of maps of the area under study, including topography, height of the buildings, land use, green areas, and types of soil pavement, as well as measurement of the environmental variables: air temperature, relative humidity, direction and wind speed for a comparative study. As part of this, study local users of the district were interviewed about their thermal sensations in open spaces. For the statistical analysis, data was collected at 10 distinct points characterized by BUSTOS ROMERO (2002), being 8 within the district and 2 at different places (outside the district), at climatologic stations, in 3 periods (August/2000, January/2002 and June/2002), for 4 consecutive days for each measurement (from Sunday to Wednesday) at the time of lower and higher temperatures in the city, 6:00 am and 1:00 pm, respectively. At the same time interviews were carried out with users of the open spaces in the area, totaling 171 valid formularies. The urban form showed a rather leveled topography, great diversity of land use and height of the buildings, with the existence of an area mostly occupied with high buildings, very little green area and soil practically impermeable. The statistical analysis showed high temperature and humidity levels. The wind direction is predominantly Southeast with extremely variable speeds. When the data from this district is compared with the data from other areas in the city and its outskirt, it was observed that this district is hotter and less ventilated than the others; besides, most users said that they felt uncomfortable in the local environmental conditions. The results of the analysis generated a zoning for the district with recommendations for soil occupation. The profile of the user was defined regarding the thermal comfort, as well as some discussion about the comfort parameters, including the proposal of limiting areas of temperature and humidity for the thermal comfort in the open spaces